Studi Tingkat Penggunaan Fasilitas Pangkalan Pendaratan Ikan (PPI) Ujong Baroeh Kabupaten Aceh Barat - Sauni, Sabtha Wahyudi; Hafinuddin, Hafinuddin; Hamidi, Hamidi; Fuadi, Afdhal; Annas, Ruesma Azhadin (JURNAL PERIKANAN TROPIS, 2023)
Fishery port facilities play a pivotal role in supporting capture fisheries operations. Inadequate capacity, incomplete facilities, and inefficient layout can hinder the smooth operation of fisheries activities. PPI Ujong Baroeh, as a strategic center for capture fisheries, suffered severe damage from the tsunami disaster. Although reconstruction efforts have been made, an evaluation of the condition and utilization of post-disaster facilities is necessary. This study aims to analyze the physical condition and utilization level of facilities at PPI Ujong Baroeh through descriptive and case study methods. Data were collected through direct observation of the types, conditions, and utilization levels of facilities during the period of April 2023. The research results show a very high level of facility utilization at PPI Ujong Baroeh, with almost all facilities being utilized optimally.